Satisfaction of residents towards internal courtyard buildings - Jamaludin, Adi Ainurzaman; Hussein, Hazreena; Tahir, Kauthar Md (Faculty of Built Environment, University of Malaya, 2018)
Residential buildings that were designed with internal courtyards offer a comfortable and pleasant indoor environment. Past research on the benefits of internal courtyards have been scientifically proven, however, the results seemed disreputable in terms of its satisfaction by occupants of a building. A survey using a set of questionnaire was conducted at two selected residential colleges in the University of Malaya to gauge the satisfaction level of residents towards an existing internal courtyard. It is evident that the majority of respondents at both colleges have given positive feedback on the satisfaction of the building layout quality, comfort level in terms of the natural daylighting, thermal comfort and indoor air quality as well as the degree of their work productivity. These findings indicate that the internal courtyard is relevant to be applied when designing a building, particularly low-rise residential buildings in the equatorial climate region.